Mastering autocad 2014 : autodesk official press. - Omura, George (John Wiley & Sons Inc, 2013)
The ultimate reference and tutorial for AutoCAD software This Autodesk Official Press book helps you become an AutoCAD and AutoCAD LT expert and has been fully updated to cover all of AutoCAD's new capabilities. Featuring the popular, empowering presentation style of veteran award-winning author George Omura, this indispensable resource teaches AutoCAD essentials using concise explanations, focused examples, step-by-step instructions, and hands-on projects. Introduces you to the basics of the interface and drafting toolsDetails how to effectively use hatches, fields, an.